FRAME BERITA DUGAAN PELANGGARAN KODE ETIK ANGGOTA DPRD DKI JAKARTA WILLIAM ADITYA SARANA - Triyani, Hastina; Suryawati, Indah (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2020)
The violation case of the ethics code by legislators occurred not only once in Indonesia. Related to the case, the research will discuss the case of alleged violation of the ethics code committed by William Aditya Sarana, a DKI Jakarta DPRD member who was reported to the DKI DPRD Honorary Board because uploading an unnatural budget on his personal social media account. This research aims to describe and analyze of Detik.com and Kompas.com frames related to the news of alleged violation of the ethics code of DKI Jakarta DPRD member William Aditya Sarana. The method that used was Robert M. Entman framing analysis. The research results showed that Detikcom and Kompas.com frames placed upload cases by William Aditya Sarana on his social media account related to the invention of an unnatural budget in the DKI Jakarta RAPBD is a moral problem. William Aditya placed as the guilty party because it has caused a public uproar. But seen from the selection of the informants and the statements made, also highlighting the indicated aspect, Detikcom tends to show positive side from William Aditya. Which means, Detikcom shows its partisanship to William Aditya. Different things with Kompas.com which shows more negative side from William Aditya. Kompas.com quoted the statement of the chosen informant that, what William has done has caused public uproar, also made negative opinion to the DKI Jakarta Governor Anies Baswedan who seems not transparent.Keywords: News, Framing, Online Media, Violation of the Ethics Code.